(3eONd Gdi GdGSGdjH GdcejI aj GdJShjb (B:s (3JWHjbGJ aj efXeGJ GdGYeGd GdGfJGLjI h GdNOejI (B/s - (3GdaVd, eDjOs ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2007)
(3jJfGhd gPG GdcJGH eGjdj GdebOeI(B-(3GdaUd GdChd (B: (3eaGgje YGeI aj GdJShjbihGdefgL Gdcej hfXe GdeYdheGJ GdJShjbjI (B: (3eaghe GdJShjb (B: (3eaghe GdefgL Gdcdj(B-(3GdaUd GdKGfj (B: (3GdSdGSd GdRefjI aj GdJfHD HGdeHjYGJ (B: (3eaghe GdSdGSd GdRefjI hechfGJgG (B: (3MSGH bjeI hJCKjQ GdEJLGI GdYGe(B-(3GdaUd GdKGdK (B: (3CSGdjH GdefgL Gdcej aj SjGSGJ GdJSYjQ (B: (3EJLGgGJ GdSjGSg GdSYQjI aj efXeI GdCYeGd (B: (3SjGSGJ GdJSYjQ aj efXeI GdCYeGd(B-(3GdaUd GdQGHY (B: (3feGPL Gdfbd aj GdJhRjY hJNUjU GdehGQO (B: (3eaghe GdJhRjY hJNUjU GdehGQO aj GdJShjb (B: (3CfhGY eTGcd hUjZ GdJhRjY aj GdhGbY GdYedj(B-(3GdaUd GdNGeS (B: (3fXQjI GdCdYGH aj JMdjd GdUQGY hGdgjefI Ydi GdShb (B: (3GdUQGY hGdgjefI Ydi GdShb (B: (3CfhGY MGdGJ GdefGaSI hGdUQGY(B-(3GdaUd GdSGOS (B: (3fXQjI GdbQGQ aj JMdjd GdefGaSI hGdUQGY eY GdWHjYI (B: (3eaghe GdbQGQ (B: (3YedjI GJNGP GdbQGQ(B-(3GdaUd GdSGHY (B: (3SdGSd eGQcha aj JMOjO GdMUg GdShbjg (B: (3JQGce GdeYQaI hGdNHQI aj JMOjO GdMUI GdShbjI(B-(3GdaUd GdKGef (B: (3fXQjI NWhW GdEfJXGQaj JShjb GdNOeI(B-(3GdaUd GdJGSY (B: (3feGPL cejI eMOOI aj eYGdLI eTcdGJ GdJShjb (B: (3fehPL GdHQeLI GdNWjI (B: (3fehPL THcGJ GdYed(B-(3GdaUd GdYGTQ(B: (3HMhK GdJShjb hfeGPL Sdhc GdeSJgdc (B: (3HMhK GdJShjb (B: (3JUeje GdHMhK hCgOGagG(B.s
(3HjHdjhZQGajG U(B.473 (3edGMb U(B.479s
Keywords: (3EOGQI GdEfJGLs; (3GOGQI GdeHjYGJs; (3JShjbs